2021
DOI: 10.1111/1756-185x.14217
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of hepatitis B virus infection in patients with rheumatoid arthritis receiving tofacitinib

Abstract: Hepatitis B virus (HBV) is a common viral infection in humans, and HBV infection is endemic in Taiwan. 1 Rheumatoid arthritis (RA) is characterized by chronic inflammation of the joints resulting in deformity and disability. Common medications for the treatment of RA include: (a) conventional synthetic disease-modifying antirheumatic drugs (csDMARDs); (b) biologic agents, such as tumor necrosis factor inhibitors, abatacept, rituximab, tocilizumab; and (c) targeted synthetic DMARDs, such as tofacitinib, baricit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
(34 reference statements)
0
14
0
4
Order By: Relevance
“…114 115 As outlined in the SLR informing these recommendations, data are less robust for drugs [116][117][118][119][120][121][122][123][124][125] other than bDMARDs. [126][127][128][129][130][131][132][133][134][135][136] However, for non-bDMARDs users, referral to a hepatologist for consideration of anti-viral prophylaxis is also recommended. The exact dose and duration of glucocorticoids that would increase HBV reactivation risk cannot be inferred from existing studies.…”
Section: Recommendationmentioning
confidence: 99%
“…114 115 As outlined in the SLR informing these recommendations, data are less robust for drugs [116][117][118][119][120][121][122][123][124][125] other than bDMARDs. [126][127][128][129][130][131][132][133][134][135][136] However, for non-bDMARDs users, referral to a hepatologist for consideration of anti-viral prophylaxis is also recommended. The exact dose and duration of glucocorticoids that would increase HBV reactivation risk cannot be inferred from existing studies.…”
Section: Recommendationmentioning
confidence: 99%
“…Tofacitinib appears safe in patients with resolved HBV infection ( 26 ) and reactivation of HBV infection could be prevented by antiviral prophylaxis. However, it is important to beware of the high incidence rate of HBV reactivation in patients with HBsAg + receiving tofacitinib and close monitoring of HBV DNA and alanine aminotransferase should be suggested ( 27 ). In clinical trials of tofacitinib for rheumatoid arthritis, no new AEs were observed in 10 years ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data on the risk of HBV reactivation during COVID-19 are scarce, but those from other sectors (onco-haematological, rheumatological, gastroenterological) [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] strongly suggest that all patients, including SARS-CoV-2 RNA-positive, should be screened for markers of HBV infection before starting corticosteroid and / or immunosuppressive treatments. HBsAg-positive patients should earlier start prophylaxis anti-HBV reactivation with high genetic barrier antivirals and continue for at least 12 months after stopping these therapies.…”
Section: Discussionmentioning
confidence: 99%